2002
DOI: 10.1128/jb.184.22.6357-6366.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Physiological Significance of ClpC and ClpP in Streptococcus mutans

Abstract: Tolerance of environmental stress, especially low pH, by Streptococcus mutans is central to the virulence of this organism. The Clp ATPases are implicated in the tolerance of, and regulation of the response to, stresses by virtue of their protein reactivation and remodeling activities and their capacity to target misfolded proteins for degradation by the ClpP peptidase. The purpose of this study was to dissect the role of selected clp genes in the stress responses of S. mutans, with a particular focus on acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 41 publications
10
137
1
Order By: Relevance
“…Standard DNA manipulation techniques were used as previously described (Lemos & Burne, 2002;Sambrook et al, 1989). The primers used to isolate the mutants are listed in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard DNA manipulation techniques were used as previously described (Lemos & Burne, 2002;Sambrook et al, 1989). The primers used to isolate the mutants are listed in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In S. mutans, Clp proteases are the result of the association of the ClpP peptidase with one of several Clp ATPases (ClpC, ClpE or ClpX), forming barrelshaped complexes that will target proteins for degradation (Kajfasz et al, 2009;Lemos & Burne, 2002). Although S. mutans also encodes ClpB and ClpL ATPases, these proteins do not contain the recognition tripeptide that permits interaction with ClpP, and are believed to function mainly as molecular chaperones (Frees et al, 2004; Kajfasz et al, 2009 Although ClpP proteolysis has been consistently implicated in virulence (Frees et al, 2003;Gaillot et al, 2000;Ibrahim et al, 2005), has shown promising results as a vaccine candidate (Kwon et al, 2004) and is the target of two new classes of antibiotics (Böttcher & Sieber, 2008; Brötz-Oesterhelt et al, 2005), a complete picture of the biological role of Clp-dependent proteolysis in bacterial pathogenesis has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic studies with mutant strains lacking functional ClpP, ClpL, ClpE, or ClpB revealed the central role of these proteins under stress conditions and, for pathogenic LAB species, in virulence (303,(305)(306)(307)(308). In contrast to the situation in B. subtilis, LAB clpC mutants usually do not exhibit stress-sensitive phenotypes (306,309). Phenotypic characterization of an S. thermophilus clpC mutant revealed that ClpC plays a role in the development of genetic competence in this organism (310).…”
Section: Treating Damaged Macromoleculesmentioning
confidence: 99%
“…Indirectly, this can be considered as a genetic approach, since the identification of the proteins on the gels is made based upon a comparison with the protein sequences deduced from the genome sequences of an organism. This approach has been utilized in several recent investigations regarding the effects of various environmental factors on S. mutans (Svensater et al, 2000;Lemos and Burne, 2002).…”
Section: (E) Application Of Whole Genome Screening Techniques Prior Tmentioning
confidence: 99%